Fun with English: Belajar Bahasa Inggris Lewat Permainan dan Aktivitas Seru untuk Siswa Sekolah Dasar di Kawasan Teluk Tomini - Husain, Nurlaila; Ali, Sri Widyarti (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
English language learning for students often faces challenges in the form of less attractive and monotonous teaching methods, leading to low interest and motivation to learn. The community service activity, "Learning English Through Games and Fun Activities" at SD Negeri 2 Kabila Bone aimed to create an interactive and enjoyable learning environment through the "learning while playing" approach. The implementation method involved games, interactive activities, and demonstrations to increase students' active participation in practicing English language skills. The results showed a significant increase in students' enthusiasm, motivation, and English language abilities, in line with theories on the benefits of games in language learning. Positive impacts were seen in academic and non-academic aspects such as self-confidence. Teachers and school authorities appreciated this approach as an innovation in facing the challenges of English language learning in the globalization era. The output obtained is a plan for the sustainability of similar programs by expanding the scope, developing materials, and increasing collaboration to make a greater contribution to improving the quality of education and English language proficiency.